A novel configuration of THz photonic transmitter - Ibtissame Moumane; Jamal Zbitou; M. Latrach; A. Errkik; O. Chakkor (Institute of Advanced Engineering and Science, 2019)
In this paper we present a new design of a photonic transmitter based on multi-layers substrate GaAs and using for generation of THz waves. The proposed circuit is composed from a photodetector (PD) “which converts the light to the electrical signal”, THz Antenna, low-pass filter and DC probe. Firstly we have optimized the THz antenna using an EM solver which is Momentum integrated in ADS “Advanced Design System”.Then we have optimized the low pass filter which plays the role of inductance that is an RF choke permiting to separate the RF signal from the DC one. Finally, we have associated the different components, add the DC probe and simulate the whole proposed system. The dimensions of the final circuit are 400.317x167.16 UM2 . The obtain results permit to validate the final circuit at THz and make it suitable for THz applications.